Positive electrode active material and preparation method thereof, positive plate and all-solid-state lithium battery

By forming a polyanionic lithium salt and conductive carbon coating with a thickness of 10 nm to 30 nm on the surface of the high-nickel positive electrode active material, the side reaction problem caused by contact between the high-nickel positive electrode active material and the sulfide solid electrolyte is solved, and the all-solid lithium battery is improved electrochemical properties and cycle stability.

CN119315010AActive Publication Date: 2025-01-14四川新能源汽车创新中心有限公司

Patent Information

Application Number
CN202411440091.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

When high-nickel positive electrode active materials come into direct contact with sulfide solid electrolytes, chemical and electrochemical side reactions will occur, resulting in reduced lithium ion or electron transport efficiency, and the volume change of layered oxide positive electrode materials during charging and discharging will lead to interface disconnection. Affects the capacity and safety performance of all solid state lithium batteries.

Method used

The cladding layer is used to include polyanionic lithium salt and conductive carbon, and the cladding layer has a thickness of 10 nm to 30 nm. The cladding layer is formed by heat treatment to improve the mechanical and electrochemical properties of the positive electrode active material, and reduce the interfacial side reaction and electron transport impedance.

Benefits of technology

Significantly improves the capacity, magnification and cycle stability of all solid lithium batteries, enhances the mechanical and electrochemical properties of the positive electrode active materials, reduces the migration of P and S elements in the sulfide solid electrolytes, and improves the safety and energy of the battery. density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315010A_ABST
    Figure CN119315010A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material and a preparation method thereof, a positive plate and an all-solid-state lithium battery, and relates to the field of lithium ion batteries, the positive electrode active material comprises a layered oxide and a coating layer coating the surface of the layered oxide, and the coating layer comprises a polyanion lithium salt and conductive carbon; the thickness of the coating layer is larger than 10 nm and smaller than 30 nm. The coating layer comprises the polyanion lithium salt and the conductive carbon, and the two substances cooperate with each other, so that direct contact between the layered oxide and the solid electrolyte can be better isolated, and side reaction is avoided. And moreover, the conductive carbon in the coating layer can reduce the electron transmission impedance, so that the improvement of the electrochemical performance of the positive electrode active material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet and an all-solid-state lithium battery. Background Art

[0002] In recent years, traditional liquid lithium-ion batteries have faced many challenges such as poor safety and limited energy density. All-solid-state batteries use solid electrolytes instead of liquid electrolytes, which can significantly improve the safety and energy density of the battery. Among them, sulfide solid electrolytes have high ionic conductivity and excellent mechanical properties, and are considered to be the solid electrolytes with the greatest potential for large-scale application. In addition, the selection of positive electrode active materials is also one of the key factors in improving the energy density of all-solid-state lithium batteries. The highly-regarded layered oxide positive electrode active materials (especially high-nickel positive electrode active materials) have advantages such as high capacity and high theoretical energy density, and are one of the more outstanding candidate positive electrode active materials for all-solid-state lithium batteries. However, when high-nickel positive electrode active materials are in direct contact with sulfide solid electrolytes, chemical and electrochemical side reactions will occur, and the by-products produced can significantly reduce the transmission efficiency of lithium ions or electrons; secondly, due to the large electrochemical potential difference between the two, the Li near the interface + The lithium ions in the layered oxide positive electrode will be redistributed to form a high resistance layer of several nanometers (i.e., space charge layer) on the side of the sulfide solid electrolyte, and the charge transfer impedance will be enhanced. Secondly, after multiple cycles of the sulfide all-solid positive electrode at high temperature, there is a situation where P and S elements migrate to the positive electrode particles, resulting in the capacity decay of the positive electrode active material. Finally, during the charge and discharge process, the layered oxide positive electrode active material causes the volume change of the positive electrode active material particles due to the deintercalation of lithium ions, resulting in the interface decontamination between the positive electrode active material and the solid electrolyte. The above phenomena will affect the capacity performance and safety performance of the solid-state battery.

[0003] The conventional means of solving the above-mentioned interface problems reported in the literature is to modify the surface of the positive electrode active material by coating and modifying it to alleviate the interface side reactions. However, these traditional all-solid-state positive electrode active material coating technologies have some defects: First, in order to ensure the capacity, the thickness of the coating layer is 5 to 10 nm. The coating layer is easily damaged during the battery preparation process, and when the battery is cycled, the volume change of the positive electrode particles will also cause the coating layer to be out of contact with the material body, which will affect the electrical performance of the solid-state battery; second, the commonly used all-solid-state positive electrode coating layer materials have the characteristics of poor electronic conductivity. Excessive coating will lead to insufficient electron transmission pathways, seriously affecting battery performance. These coating layer defects are currently the main factors restricting the low capacity, rate and cycle of all-solid-state positive electrodes.

[0004] Therefore, it is necessary to improve the positive electrode active material and the preparation method thereof. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode active material and a preparation method thereof, a positive electrode sheet and an all-solid-state lithium battery to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A positive electrode active material, comprising a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer comprises a polyanion lithium salt and conductive carbon;

[0008] The coating layer has a thickness greater than 10 nm and less than 30 nm.

[0009] According to an embodiment of the present application, the polyanion lithium salt includes one or more of lithium phosphate, lithium fluorophosphate, lithium sulfate, lithium borate, lithium silicate, and lithium pyrophosphate;

[0010] And / or, the layered oxide comprises LiNi a Co b Mn 1-a-b O2, where a≥0.7, b≥0.

[0011] According to an embodiment of the present application, the conductive carbon accounts for 0.1 to 1.0% of the mass of the layered oxide;

[0012] and / or, the conductive carbon accounts for 10.0-40.0% of the mass of the polyanion lithium salt;

[0013] And / or, the polyanion lithium salt accounts for 0.5-5.0% of the mass of the layered oxide.

[0014] According to an embodiment of the present application, the coating layer further includes lithium fluoride, and the lithium fluoride accounts for 0.5 to 5.0% of the mass of the layered oxide.

[0015] The present application also provides a method for preparing the positive electrode active material as described above, comprising:

[0016] The layered oxide, the polyanion compound, the lithium source and the organic carbon source are mixed, and heat-treated under the protection of an inert gas to obtain a positive electrode active material.

[0017] According to an embodiment of the present application, the polyanion compound includes one or more of phosphates, fluorophosphates, sulfates, borates, silicates, and pyrophosphates; wherein the phosphate includes ammonium phosphate; the fluorophosphate includes at least one of ammonium hexafluorophosphate, lithium hexafluorophosphate, and sodium hexafluorophosphate.

[0018] And / or, the lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes one or more of lithium carbonate, lithium hydroxide, and lithium sulfate;

[0019] And / or, the organic carbon source consists of carbon, hydrogen and oxygen elements.

[0020] And / or, the organic carbon source includes one or more of glucose, sucrose, and starch.

[0021] According to an embodiment of the present application, when the polyanion compound is one or more of ammonium phosphate, ammonium fluorophosphate, and ammonium sulfate, the polyanion compound accounts for 0.6 to 7.5% of the mass of the layered oxide, the lithium salt accounts for 0.5 to 6.6% of the mass of the layered oxide, and the organic carbon source accounts for 0.5 to 2.5% of the mass of the layered oxide;

[0022] When the polyanion compound is ammonium borate, the polyanion compound accounts for 1.4-14.5% of the mass of the layered oxide, the lithium salt accounts for 0.8-8.0% of the mass of the layered oxide, and the organic carbon source accounts for 0.5-2.5% of the mass of the layered oxide.

[0023] According to an embodiment of the present application, the inert gas includes nitrogen or argon;

[0024] And / or, the temperature of the heat treatment is 400-1000°C;

[0025] And / or, the heat treatment time is 1 to 10 hours.

[0026] The present application also provides a positive electrode sheet, comprising a current collector and a functional layer located on one side of the current collector, wherein the material forming the functional layer comprises a sulfide electrolyte, a conductive agent and a positive electrode active material;

[0027] Wherein, the positive electrode active material is the positive electrode active material described above or the positive electrode active material prepared by the preparation method described above.

[0028] The present application also provides an all-solid-state lithium battery, which includes the positive electrode sheet described above.

[0029] Compared with the prior art, the beneficial effects of this application include:

[0030] Sulfide solid electrolytes will decompose under high voltage, and their products include polyanion byproducts such as phosphates, sulfates, and sulfites. The coating layer and byproducts of the present application have good chemical stability and electrochemical stability. At the same time, the coating layer of the present application contains polyanion lithium salts, which can effectively inhibit the migration of P and S elements in the sulfide solid electrolyte to the layered oxide, and can effectively protect the layered oxide.

[0031] If the coating layer only contains polyanion compounds, the coating layer will have poor electronic conductivity, resulting in a large electron transfer impedance of the positive electrode active material. However, the present application also contains conductive carbon in the coating layer, which can effectively solve the electron transfer problem, significantly improve the capacity and rate performance of the solid-state battery, and improve the cycle stability.

[0032] In general, the cooperation between polyanion lithium salt and conductive carbon can significantly improve the electrochemical performance of the positive electrode active material. Moreover, the thickness of the coating layer of the present application is 10nm to 30nm, which can make the positive electrode active material have higher mechanical properties, which is conducive to improving the cycle performance of the positive electrode active material.

[0033] The present application also provides a method for preparing a positive electrode active material. The positive electrode active material prepared by the method has high electronic conductivity and high mechanical strength, can effectively reduce the interface side reaction between the layered oxide and the sulfide solid electrolyte, reduce the initial impedance inside the all-solid-state positive electrode, and significantly improve the capacity, first efficiency, rate, and cycle performance of the all-solid-state battery. Moreover, the method of the present application has the advantages of simple operation and low production cost, which is conducive to large-scale industrial production.

[0034] The positive electrode sheet and all-solid-state lithium battery of the present application both have excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0036] Figure 1 This is a schematic diagram of the structure of the positive electrode active material of the present application;

[0037] Figure 2 TEM image of the positive electrode active material in Example 1;

[0038] Figure 3 is a schematic diagram of the structure of the positive electrode active material in Example 2;

[0039] Figure 4 TEM image of the positive electrode active material in Comparative Example 2;

[0040] Figure 5 TEM image of the positive electrode active material in Comparative Example 3;

[0041] Figure 6 Schematic diagram of the structure of an all-solid-state half-battery. DETAILED DESCRIPTION

[0042] As used herein:

[0043] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0044] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0045] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0046] In these examples, parts and percentages are by mass unless otherwise indicated.

[0047] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0049] The present application provides a positive electrode active material, referring to Figure 1, comprising a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer comprises a polyanion lithium salt and conductive carbon;

[0050] The coating layer has a thickness greater than 10 nm and less than 30 nm.

[0051] For example, the thickness of the coating layer may be 10.5 nm, 14 nm, 15 nm, 16 nm, 20 nm, 25 nm, 30 nm, or any value greater than 10 nm and less than 30 nm.

[0052] The present application can improve the mechanical properties and electrochemical properties of the positive electrode active material by surface coating modification of the layered oxide. Specifically, the coating layer of the present application includes polyanion lithium salt and conductive carbon. The two substances cooperate with each other to better isolate the direct contact between the layered oxide and the solid electrolyte and avoid side reactions. Moreover, the conductive carbon in the coating layer can reduce the electron transfer impedance, which is beneficial to the improvement of the electrochemical performance of the positive electrode active material.

[0053] Moreover, compared with conventional positive electrode active materials with a coating structure, the coating layer of the present application is thicker. When the thickness of the coating layer is within the range of the present application, the structure of the coating layer is stable and not easy to fall off, which can effectively avoid direct contact between the layered oxide and the sulfide solid electrolyte, and avoid the occurrence of side reactions at the positive electrode interface of the all-solid-state lithium battery.

[0054] In addition, when the thickness of the coating layer is within the range of the present application, it can also improve the mechanical strength of the layered oxide, alleviate the ball cracking of the positive electrode active material due to high-pressure pressing during battery preparation and the ball cracking of the layered oxide due to volume change during battery cycling, and reduce the interface contact loss between the positive electrode active material and the solid electrolyte.

[0055] According to an embodiment of the present application, the polyanion lithium salt includes one or more of lithium phosphate, lithium fluorophosphate, lithium sulfate, lithium borate, lithium silicate, and lithium pyrophosphate;

[0056] And / or, the layered oxide comprises LiNi a Co b Mn 1-a-b O2, where a≥0.7, b≥0.

[0057] Furthermore, a may be 0.8, b may be 0.1, and the layered oxide may be LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).

[0058] According to the embodiment of the present application, the conductive carbon accounts for 0.1-1.0% of the mass of the layered oxide. If the mass ratio of the conductive carbon to the layered oxide is too low, it will not have a significant effect of improving the conductivity. If the mass ratio of the conductive carbon to the layered oxide is too high, too much conductive carbon will catalyze the oxidative decomposition of the sulfide solid electrolyte and affect the battery performance.

[0059] For example, the conductive carbon accounts for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or any value between 0.1 and 1.0% of the mass of the layered oxide.

[0060] And / or, the conductive carbon accounts for 10.0-40.0% of the mass of the polyanion lithium salt. If the conductive carbon mass ratio in the coating layer is too low, the poor conductivity of the polyanion lithium salt will lead to insufficient electron pathways in the coated positive electrode material, affecting battery performance; if the conductive carbon mass ratio in the coating layer is too high, the conductive carbon will catalyze the oxidative decomposition of the sulfide solid electrolyte, affecting battery performance;

[0061] For example, the conductive carbon accounts for 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value between 10.0% and 40.0% of the mass of the polyanion lithium salt.

[0062] And / or, the polyanion lithium salt accounts for 0.5-5.0% of the mass of the layered oxide. If the content of the polyanion lithium salt on the surface of the layered oxide is too low, the coating layer will be thin, the coating will be incomplete, and it will be easy to fall off and break, and it will not play a good isolation role, and strong interfacial side reactions will occur; if the content of the polyanion lithium salt on the surface of the layered oxide is too high, the coating layer will be too thick, the transmission distance and transmission resistance of lithium ions will increase, and the battery performance will be affected.

[0063] For example, the polyanion lithium salt accounts for 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value between 0.5 and 5.0% of the mass of the layered oxide.

[0064] According to an embodiment of the present application, the coating layer further comprises lithium fluoride, which accounts for 0.5 to 5.0% of the mass of the layered oxide. Lithium fluoride has excellent high-voltage stability and ionic conductivity, and lithium fluoride can cooperate with polyanionic lithium salts and conductive carbon to further improve the transmission of ions and electrons and reduce interface side reactions, which is conducive to further improving the electrochemical performance of the all-solid-state positive electrode.

[0065] For example, lithium fluoride accounts for 0.5%, 1%, 1.5%, 2%, 2.5%, 2.7%, 3%, 3.5%, 4%, 4.5%, 5% or any value between 0.5 and 5.0% by mass of the layered oxide.

[0066] The present application also provides a method for preparing the positive electrode active material as described above, comprising:

[0067] The layered oxide, the polyanion compound, the lithium source and the organic carbon source are mixed, and heat-treated under the protection of an inert gas to obtain a positive electrode active material.

[0068] According to an embodiment of the present application, the polyanion compound includes one or more of phosphate, fluorophosphate, sulfate, borate, silicate, and pyrophosphate; wherein the phosphate includes ammonium phosphate; the fluorophosphate includes at least one of ammonium hexafluorophosphate, lithium hexafluorophosphate, and sodium hexafluorophosphate. These types of polyanion compounds have a relatively low melting point, which is conducive to forming a homogeneous coating layer on the surface of the layered oxide during heat treatment, which is used to isolate the layered oxide and the solid electrolyte and alleviate the interface side reaction.

[0069] The polyanion compound is preferably a fluorophosphate. When the polyanion compound is a fluorophosphate, lithium fluoride can be formed in the coating layer, and lithium fluoride has excellent high-voltage stability and ionic conductivity. The lithium fluoride in the coating layer supports and cooperates with the polyanion lithium salt and the conductive carbon, which can more effectively improve the transmission of ions and electrons and reduce interface side reactions, thereby improving the electrochemical performance of the all-solid-state positive electrode, and specifically, can improve the capacity, first efficiency, rate and cycle performance of the all-solid-state positive electrode.

[0070] According to an embodiment of the present application, the lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes one or more of lithium carbonate, lithium hydroxide, and lithium sulfate;

[0071] And / or, the organic carbon source consists of carbon, hydrogen and oxygen elements.

[0072] According to an embodiment of the present application, the organic carbon source includes one or more of glucose, sucrose, and starch.

[0073] According to an embodiment of the present application, when the polyanion compound is one or more of ammonium phosphate, ammonium fluorophosphate, and ammonium sulfate, the polyanion compound accounts for 0.6-7.5% of the mass of the layered oxide, the lithium source accounts for 0.5-6.6% of the mass of the layered oxide, and the organic carbon source accounts for 0.5-2.5% of the mass of the layered oxide. When the content of each component is within the above range, it is conducive to generating a coating layer with a moderate thickness, so that the positive electrode active material can have a higher capacity, excellent conductivity, etc. If the content of the polyanion compound is too low, the coating layer will be thinner; if the content of the anion compound is too high, the coating layer will be too thick; if the content of the lithium source is too low, the polyanion compound will consume the lattice lithium ions of the layered oxide during heat treatment, resulting in a decrease in capacity; if the content of the lithium source is too high, the excess lithium ions will form free lithium attached to the surface of the layered oxide, affecting battery performance; if the content of the organic carbon source is too low, the final product will have insufficient conductivity; if the content of the organic carbon source is too high, there will be too much conductive carbon, which will promote the decomposition of the sulfide solid electrolyte.

[0074] For example, when the polyanionic compound is one or more of ammonium phosphate, ammonium fluorophosphate, and ammonium sulfate, the polyanionic compound accounts for 0.6%, 1%, 1.5%, 2%, 2.5%, 2.6%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.4%, 6.5%, 7%, 7.5% or any value between 0.6 and 7.5% of the mass of the layered oxide, the lithium salt accounts for 0.5%, 1%, 1.5%, 2%, 2.2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.4%, 5.5%, 6%, 6.6% or any value between 0.5 and 6.6% of the mass of the layered oxide, and the organic carbon source accounts for 0.5%, 1%, 1.3%, 1.5%, 2%, 2.5% or any value between 0.5 and 2.5% of the mass of the layered oxide.

[0075] When the polyanion compound is ammonium borate, the polyanion compound accounts for 1.4-14.5% of the mass of the layered oxide, the lithium source accounts for 0.8-8.0% of the mass of the layered oxide, and the organic carbon source accounts for 0.5-2.5% of the mass of the layered oxide.

[0076] Furthermore, the ammonium fluorophosphate includes ammonium hexafluorophosphate.

[0077] According to an embodiment of the present application, the inert gas includes nitrogen or argon;

[0078] And / or, the temperature of the heat treatment is 400-1000°C;

[0079] For example, the temperature of the heat treatment may be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, or any value between 400 and 1000°C.

[0080] And / or, the heat treatment time is 1 to 10 hours.

[0081] For example, the heat treatment time may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or any value between 1 and 10 h.

[0082] The present application also provides a positive electrode sheet, comprising a current collector and a functional layer located on one side of the current collector, wherein the material forming the functional layer comprises a sulfide electrolyte, a conductive agent and a positive electrode active material;

[0083] Wherein, the positive electrode active material is the positive electrode active material described above or the positive electrode active material prepared by the preparation method described above.

[0084] The present application also provides an all-solid-state lithium battery, which includes the positive electrode sheet described above.

[0085] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0086] Example 1

[0087] The positive electrode active material in Example 1 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt and conductive carbon; the thickness of the coating layer is greater than 10 nm and less than 30 nm, the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 2% of the mass of the layered oxide, the conductive carbon accounts for 0.5% of the mass of the layered oxide, and the conductive carbon accounts for 25% of the mass of the polyanion lithium salt.

[0088] Accurately weigh NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate, and glucose into 10g, 0.26g, 0.22g, and 0.13g respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 700°C and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0089] Figure 2is the TEM image of the positive electrode active material in Example 1, Figure 2 It can be seen that the thickness of the coating layer is 15 nm.

[0090] Example 2

[0091] refer to Figure 3 The positive electrode active material in Example 2 includes a layered oxide and a coating layer coated on the surface of the layered oxide, the coating layer includes a polyanion lithium salt, lithium fluoride and conductive carbon; the thickness of the coating layer is greater than 10nm and less than 30nm, the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 2% of the mass of the layered oxide, the lithium fluoride accounts for 2.7% of the mass of the layered oxide, the conductive carbon accounts for 0.5% of the mass of the layered oxide, and the conductive carbon accounts for 25% of the mass of the polyanion lithium salt.

[0092] Accurately weigh 10g, 0.25g, 0.66g and 0.13g of NCM811 ternary positive electrode material, ammonium hexafluorophosphate, lithium hydroxide monohydrate and glucose respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 700℃ and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0093] Example 3

[0094] The positive electrode active material in Example 3 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt and conductive carbon; the thickness of the coating layer is greater than 10 nm and less than 30 nm, the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 0.5% of the mass of the layered oxide, the conductive carbon accounts for 0.2% of the mass of the layered oxide, and the conductive carbon accounts for 40% of the mass of the polyanion lithium salt.

[0095] Accurately weigh 10g, 0.06g, 0.05g and 0.05g of NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate and glucose respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 700℃ and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0096] Example 4

[0097] The positive electrode active material in Example 4 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt and conductive carbon; the thickness of the coating layer is greater than 10 nm and less than 30 nm, the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 5% of the mass of the layered oxide, the conductive carbon accounts for 1% of the mass of the layered oxide, and the conductive carbon accounts for 20% of the mass of the polyanion lithium salt.

[0098] Accurately weigh NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate, and glucose into 10g, 0.64g, 0.54g, and 0.25g, respectively, and mix them evenly in a ball mill. Then transfer them to a tubular furnace for sintering. The sintering conditions are 700°C and 5h. Nitrogen needs to be introduced throughout the sintering process to finally obtain the positive electrode active material.

[0099] Comparative Example 1

[0100] Accurately weigh NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate, and glucose into 10g, 0.26g, 0.22g, and 0.13g respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 300°C and 5h. Nitrogen needs to be introduced throughout the sintering process to finally obtain the positive electrode active material.

[0101] Comparative Example 2

[0102] The positive electrode active material in Comparative Example 2 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt and conductive carbon; the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 0.3% of the mass of the layered oxide, the conductive carbon accounts for 0.1% of the mass of the layered oxide, and the conductive carbon accounts for 33% of the mass of the polyanion lithium salt.

[0103] Accurately weigh 10g, 0.04g, 0.03g and 0.03g of NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate and glucose respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 700℃ and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0104] Figure 4 is the TEM image of the positive electrode active material in Comparative Example 2, Figure 4 It can be seen that the thickness of the coating layer is 5 to 10 nm.

[0105] Comparative Example 3

[0106] The positive electrode active material in Comparative Example 3 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt and conductive carbon; the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, the polyanion lithium salt accounts for 5.5% of the mass of the layered oxide, the conductive carbon accounts for 1.5% of the mass of the layered oxide, and the conductive carbon accounts for 27% of the mass of the polyanion lithium salt.

[0107] Accurately weigh NCM811 ternary positive electrode material, ammonium phosphate, lithium hydroxide monohydrate, and glucose into 10g, 0.72g, 0.6g, and 0.38g, respectively, and mix them evenly in a ball mill. Then transfer them to a tubular furnace for sintering. The sintering conditions are 700°C and 5h. Nitrogen needs to be introduced throughout the sintering process to finally obtain the positive electrode active material.

[0108] Figure 5 is the TEM image of the positive electrode active material in Comparative Example 3, Figure 5 It can be seen that the thickness of the coating layer is 30-35 nm.

[0109] Comparative Example 4

[0110] The positive electrode active material in Comparative Example 4 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer includes a polyanion lithium salt; the polyanion lithium salt includes lithium phosphate, and the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, polyanionic lithium salt accounts for 2% of the layered oxide mass.

[0111] Accurately weigh NCM811 ternary positive electrode material, ammonium phosphate, and lithium hydroxide monohydrate into 10g, 0.26g, and 0.22g, respectively, and evenly mix them in a ball mill. Then transfer them to a tubular furnace for sintering. The sintering conditions are 700°C and 5h. Nitrogen needs to be introduced throughout the sintering process to finally obtain the positive electrode active material.

[0112] Comparative Example 5

[0113] Comparative Example 5: The positive electrode active material was prepared using a liquid phase method.

[0114] Accurately weigh 0.26g of ammonium phosphate, 0.22g of lithium hydroxide monohydrate and 0.13g of glucose into a beaker, add 20mL of pure water and stir to dissolve, then weigh 10g of NCM811 ternary positive electrode material, disperse and stir for 10min, place at 100℃ while stirring and evaporating until a slurry is formed, put it into a vacuum drying oven to completely evaporate the water, and finally crush it with a mortar and transfer it to a tubular furnace for sintering. The sintering conditions are 700℃ and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0115] Comparative Example 6

[0116] The positive electrode active material of Comparative Example 6 is NCM811.

[0117] In order to compare with the coated positive electrode material, NCM811 was sintered in a tubular furnace at 700°C for 5 hours. Nitrogen was introduced throughout the sintering process to finally obtain the positive electrode active material.

[0118] Comparative Example 7

[0119] The positive electrode active material in Comparative Example 7 includes a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer only has conductive carbon; the layered oxide includes LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon accounts for 0.5% of the mass of the layered oxide.

[0120] Accurately weigh 10g and 0.13g of NCM811 ternary positive electrode material and glucose respectively, mix them evenly in a ball mill, and then transfer them to a tubular furnace for sintering. The sintering conditions are 700℃ and 5h. Nitrogen needs to be introduced during the entire sintering process to finally obtain the positive electrode active material.

[0121] Performance Tests of Examples and Comparative Examples

[0122] The positive electrode active materials prepared in the examples and comparative examples were assembled into solid-state batteries according to the following method, and the specific steps are as follows.

[0123] Assembly of all-solid-state half-cell: The assembled all-solid-state lithium battery is a sulfide electrolyte all-solid-state lithium battery pressed by a pressure mold. Use an agate mortar to grind and mix each positive electrode active material, sulfide electrolyte and conductive carbon in a mass ratio of 70:30:3 as the functional layer of the positive electrode sheet (composite positive electrode, Figure 6 The positive electrode sheet in the battery), Li6P5SCl (LPSC) as the solid electrolyte, stainless steel sheet as the current collector of the positive electrode sheet and the current collector of the negative electrode sheet, Li-In alloy as the negative electrode, the schematic diagram of the all-solid-state lithium battery structure is as follows Figure 6 shown.

[0124] Test equipment: LAND battery test system model CT-2001A from Wuhan Landian Electronics Co., Ltd., EIS AC impedance tester (PGSTAT204) from Switzerland Metrohm, and MCT series micro compression tester from Shimazuwa, Japan.

[0125] Test method: The charge and discharge test uses constant current charge and discharge mode to characterize the capacity, rate performance and cycle performance of all-solid-state lithium batteries. The test temperature is 45°C and the voltage range is 2.1~3.7V (corresponding to 2.72~4.32V vs.Li / Li + , because Li-In has a Li / Li + The potential is 0.62 V).

[0126] The electronic conductivity is measured by assembling an ion-blocking solid-state mold battery for DC testing, and then by the formula (Wherein, V = 50 mV; I is the steady-state current under a bias of 50 mV, L is the thickness of the composite positive electrode; S is the cross-sectional area of ​​the mold) The electronic conductivity was calculated, and the test temperature was 45°C.

[0127] The particle strength of the positive electrode active material was tested using a Japanese Shimazuwa MCT series micro compression testing machine.

[0128] Table 1 Comparison of electrochemical performance of all-solid-state half-cells of embodiments and comparative examples

[0129]

[0130] It can be seen from the data in Table 1 that the comprehensive performance of Examples 1-4 is better than that of Comparative Examples 1-7.

[0131] Compared with Example 1, the capacity, first efficiency, rate and cycle of Example 2 are better, mainly because lithium fluoride exists inside the coating layer of Example 2, and lithium fluoride has better high-voltage stability and lithium ion conductivity. Compared with Example 1, the performance of Examples 3 and 4 is slightly worse in all aspects, mainly due to the influence of the coating amount and coating thickness.

[0132] Compared with Example 1, the battery performance, electronic conductivity and particle strength of Comparative Example 1 are worse because the heat treatment temperature is too low to form a good coating layer and to carbonize the organic carbon source better.

[0133] Compared with Example 1, the comprehensive performance of Comparative Examples 2 and 3 is inferior to that of Example 1. This is because the thickness of the coating layer in Comparative Example 2 is too small, and the thickness of the coating layer in Comparative Example 3 is too large. Both too small and too large thicknesses of the coating layer will lead to a decrease in electrical performance. Among them, if the thickness of the coating layer is too small, it is easy to cause the coating layer to break or fall off, which will cause direct contact between the positive electrode material and the solid electrolyte, and serious side reactions; if the thickness of the coating layer is too large, it will significantly increase the transmission path of lithium ions and electrons, resulting in a decrease in capacity and rate. When the thickness of the coating layer is greater than 10nm and less than 30nm, the positive electrode active material can have excellent electrochemical properties.

[0134] Compared with Examples 1 to 4, the comprehensive performance of Comparative Example 4 is inferior to that of Examples 1 to 4, especially the 1C rate and electronic conductivity, which is mainly due to the lack of conductive carbon inside the coating layer of Comparative Example 4 and the large electronic transmission impedance.

[0135] The electrical properties and other properties of Comparative Example 5 are very close to those of Example 1, indicating that the coating effects of the two coating methods (dry method and liquid phase method) are similar, but the process flow of liquid phase coating is more complicated and the manufacturing cost is higher.

[0136] Compared with Examples 1 to 4, the capacity, first efficiency and rate of Comparative Example 6 are inferior to those of Examples 1 to 4, mainly because Comparative Example 6 does not contain a coating layer, while the positive electrode active materials of Examples 1 to 4 include a coating layer. After coating, the interfacial side reactions between the positive electrode material and the sulfide solid electrolyte are reduced, the electronic conductivity of the positive electrode material is significantly increased, and the cycle performance is improved.

[0137] Compared with Examples 1 to 4, the cycle performance and particle strength of Comparative Example 7 are inferior to those of Examples 1 to 4. This is due to the lack of polyanion lithium salt in the coating layer of Comparative Example 7.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0139] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A positive electrode active material, characterized in that: It comprises a layered oxide and a coating layer coated on the surface of the layered oxide, wherein the coating layer comprises a polyanion lithium salt and conductive carbon; The coating layer has a thickness greater than 10 nm and less than 30 nm.

2. The positive electrode active material according to claim 1, characterized in that The polyanion lithium salt includes one or more of lithium phosphate, lithium fluorophosphate, lithium sulfate, lithium borate, lithium silicate, and lithium pyrophosphate; And / or, the layered oxide comprises LiNi a Co b Mn 1-a-b O2, where a≥0.7, b≥0.

3. The positive electrode active material according to claim 1, characterized in that The conductive carbon accounts for 0.1 to 1.0% of the mass of the layered oxide; and / or, the conductive carbon accounts for 10.0-40.0% of the mass of the polyanion lithium salt; And / or, the polyanion lithium salt accounts for 0.5-5.0% of the mass of the layered oxide.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The coating layer further comprises lithium fluoride, and the lithium fluoride accounts for 0.5-5.0% of the mass of the layered oxide.

5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: include: The layered oxide, the polyanion compound, the lithium source and the organic carbon source are mixed, and heat-treated under the protection of an inert gas to obtain a positive electrode active material.

6. The preparation method according to claim 5, characterized in that: The polyanion compound includes one or more of phosphate, fluorophosphate, sulfate, borate, silicate, and pyrophosphate; wherein the phosphate includes ammonium phosphate; the fluorophosphate includes at least one of ammonium hexafluorophosphate, lithium hexafluorophosphate, and sodium hexafluorophosphate; And / or, the lithium source includes a lithium salt or a hydrate of a lithium salt, and the lithium salt includes one or more of lithium carbonate, lithium hydroxide, and lithium sulfate; And / or, the organic carbon source consists of carbon, hydrogen and oxygen elements; And / or, the organic carbon source includes one or more of glucose, sucrose, and starch.

7. The preparation method according to claim 6, characterized in that: When the polyanion compound is one or more of ammonium phosphate, ammonium fluorophosphate, and ammonium sulfate, the polyanion compound accounts for 0.6-7.5% of the mass of the layered oxide, the lithium source accounts for 0.5-6.6% of the mass of the layered oxide, and the organic carbon source accounts for 0.5-2.5% of the mass of the layered oxide; When the polyanion compound is ammonium borate, the polyanion compound accounts for 1.4-14.5% of the mass of the layered oxide, the lithium source accounts for 0.8-8.0% of the mass of the layered oxide, and the organic carbon source accounts for 0.5-2.5% of the mass of the layered oxide.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The inert gas includes nitrogen or argon; And / or, the temperature of the heat treatment is 400-1000°C; And / or, the heat treatment time is 1 to 10 hours.

9. A positive electrode sheet, characterized in that: It includes a current collector and a functional layer located on one side of the current collector, wherein the material forming the functional layer includes a sulfide electrolyte, a conductive agent and a positive electrode active material; Wherein, the positive electrode active material is the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material prepared by the preparation method according to any one of claims 5 to 8.

10. An all-solid-state lithium battery, characterized in that: The all-solid-state lithium battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Ternary positive electrode material coated with combination of lithium phosphate and conductive carbon material and preparation method and application thereof

    CN110098387A

  • Composite coated all-solid-state battery cathode material and preparation method thereof and all-solid-state battery

    CN112164776A

  • Battery positive electrode material as well as preparation method and application thereof

    CN115602820A

  • High-voltage all-solid-state battery positive electrode material as well as preparation method and application thereof

    CN116053438A

  • Negative electrode for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for producing negative electrode for nonaqueous electrolyte secondary battery

    US20190214630A1

Cited By

  • Solid-state battery and manufacturing method therefor, doped / coated modified oxide-based positive electrode active material, positive electrode sheet, and electric device

    WO2026166256A1